Technological change and inequality in the very long run - Jakob Brøchner Madsen; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
In this paper we investigate the impact of technological change on inequalityin the presence of a landed elite using a standard unified growth model. We measure inequality by the ratio between land rent and wages and show that, before the onset of the fertility transition, technological progress increased inequality directly through land-biased technological change and indirectly through increasing population growth. Thefertility transition and the child quantity-quality trade-off eventually disabled the Malthusian mechanism, and technological progress triggered education and benefited workers. If the elasticity of substitution between land and labor is sufficiently high, the rent-wage ratio declines such that inequality is hump-shaped in the very long run. We use the publication of new farming book titles as a measure of technological progress in agriculture, and provide evidence for technology-driven inequality in Britain between 1525 and 1895. We confirm these results for a panel of European countries over the period 1265-1850 using agricultural productivity as a measure of technology. Finally, using patents in the period 1800-1980, we find a technology-driven inequality reversal around the onset of the fertility transition.
Keywords: O40; O30; N30; N50; J10; I25; 330; nequality; Malthus; Unified Growth Theory; Agriculture; Human Capital